Adomnán, two saints, and the paschal controversy. (May 2017) - Márkus, Gilbert
Abstract : We have long understood from Bede's testimony that Adomnán, the ninth abbot of Iona, urged his monks to adopt the relatively new 19-year paschal cycle, but they – or many of them – remained faithful to the 84-year cycle which they had inherited. There are passages in Vita sancti Columbae which show Adomnán using stories about St Columba in an attempt to deal with this situation, first of all to reduce the harm done to the community by the disagreement, urging fraternal charity; and secondly, as argued here for the first time, by using contrasting stories about two other saints, Ernéne and Fintan, to persuade his monks that Columba had prophetically foreseen the dispute over the Easter date, and that he had 'cast his vote', so to speak, with the saint associated with the 19-year cycle.